Criminal Victims, Victimized Criminals, or Both? A Deeper Look at the Victim-Offender Overlap - Horst Entorf (Institute for the Study of Labor (IZA), 2013)
Offenders are more likely than non-offenders to be victims, and victims are more likely than non-victims to be offenders. The overlap between offenders and victims is not well understood in criminology, and in the economics of crime the stylized empirical fact is even widely ignored. The paper gives a survey of leading theoretical interpretations and empirical results. It summarizes findings from criminology and focuses on economic explanations, where rational choice, behavioral economics, as well as bounded and ecological rationality are discussed. The paper presents new econometric evidence based on German survey data covering victimization experiences and criminal activities. Using recursive bivariate Probit modeling, econometric results confirm that victimization depends on offending but not vice versa. Among the joint covariates of the bivariate system, broken homes, criminal records of parents and personal indebtedness turn out as highly relevant factors of offending behavior, whereas individual victimization risks are significantly linked to education, employment and size of peer groups.
Keywords: C35; C25; J12; K42; Z13; 330; victim-offender overlap; crime; victimization; rational choice; behavioral economics; negative reciprocity; recursive bivariate probit; education and victimization; indebtedness